عزل وتشخيص البكتريا الممرضه من مناطق جسميه مختلفه من المرضى في محافظة الديوانيه - جاسم , ضفاف (University of Thi-Qar Journal of Science, 2010)
The current study included the seperation and identification of bacteria that causes inflamedcases from 1/8 August to 15 / 9 September . It was gathered (135 samples) including (95) samples for paitients. Including tonsilite, ear, nose,eye and wounds swab. The pathalogical samples were collected from the patients in the consulting infirmary in AlDiwanya general hospital .The normal samples were collected from the patient s companious in Al-Diwanya city.Both samples were for different ages and sexes. Special tests about the isolated bacteria were excuted to show the ability of this bacteria of producing some enzymes (positiv or negative ) Gram,s stain , bacteria was diagnosed depending on the test results IMVIC and dignosis (20)samples from tonsilites swab appear bacteria Streptococci pyogenes ratio( %65) it was followed bacteria Staph. aureus in ratio (%35) while number isolated dignosis from swab (ear, wounds, eye and nose) They were(13,11,30,21) samples in sequence that showed the spread of bacteria Proteus mirabilis in ratio (%57.14), Pseudomonas aeruginosa in ratio (%28.57) and isolate bacteria Klebsiella pneumonia in ratio (%14.28) isolated bacteria from ear while isolated bacteria from wounds it was Staph. aureus to in ratio (%60) followed Escherichia. Coli in ratio (%40).